FORMS AND LEVELS OF COLLABORATION BETWEEN ACADEMIC INSTITUTIONS AND AGRO-INDUSTRIAL FIRMS IN ONDO STATE, NIGERIA - Akinnagbe, Oluwole Matthew; Okunlola, James Olaniyi; Ayodele, Omowunmi Veronica; Ipinmoye, Obadamilola Enitan (Journal of Science, Technology and Innovation Research, 2026)
This study examined the forms and levels of collaboration between academic institutions and agro-industrial firms in Ondo State, Nigeria. A multistage sampling technique was used to select 180 respondents comprising academics, agro-industrial firms, and relevant government agencies. Data were collected through structured questionnaires and key informant interviews and analysed using frequencies, percentages, means, standard deviations, and figures. Results show that collaboration is predominantly training-oriented rather than research-driven. From the academic perspective, the Student Industrial Work Experience Scheme (SIWES) was the most prevalent form of collaboration (100.0%), co-hosting of workshops (58.3%), consultancy services (50.0%), and formal Memoranda of Understanding (50.0%). Similarly, agro-industrial firms reported internships and SIWES placements as the dominant engagement (80.0%). The level of collaboration was generally weak, as interaction frequency was very low (x̄ = 1.17), despite high commitment from both academia and industry (x̄ = 2.92). Academia played a strong role in providing research-driven solutions, particularly in improving productivity, value-chain development, technical expertise, and technology adoption (x̄ = 3.50). Meanwhile, collaboration was significantly constrained by climate change impacts (x̄ = 3.42), market volatility (x̄ = 3.25), and low research commercialisation (x̄ = 3.00). Agro-industrial firms expressed strong demand for applied research support, especially expert technical advice (90.0%), skills gap analysis (90.0%), and problem-oriented studies addressing production and processing challenges (89.0%). Based on these findings, the study recommends that academic institutions and agro-industrial firms should transition from predominantly training-based interactions to structured, problem-oriented research collaboration by jointly designing applied research agendas that directly address identified industry challenges.